Adenovirus type 5 precursor terminal protein-expressing 293 and HeLa cell lines. - Schaack, J (1995)
HeLa and 293 cell lines that express biologically active adenovirus type 5 precursor terminal protein (pTP) have been made. The amount of pTP synthesized in these cell lines ranges from barely detectable to greater than that observed in cells infected with the wild-type virus. The pTP-expressing cell lines permit the growth of a temperature-sensitive terminal protein mutant virus sub100r at the nonpermissive temperature. A higher percentage of the stably transfected 293 cell lines expressed terminal protein, and generally at considerably higher levels, than did the HeLa cell lines. While 293 cells appeared to tolerate pTP better than did HeLa cells, high-level pTP expression in 293 cells led to a significantly reduced growth rate. The 293-pTP cell lines produce infectious virus after transfection with purified viral DNA and form plaques when overlaid with Noble agar after infection at low multiplicity. These cell lines offer promise for the production of adenoviruses lacking pTP expression and therefore completely defective for replication.